Typology and Cotton Insect Pests’ Distribution in Biological Crop System in Benin - AZONKPIN, Saturnin; CHOUGOUROU, CHÈPO DANIEL; DJIHINTO, Cocou Angelo; Bokonon-Ganta, Aimé H. (My University, 2019)
Defining effective strategies for combating crops insect pests requires to be well knowledgeable about their ecology and prevalence. This study identified on the one hand the major insect pests of biological cotton crops in the phytosanitary zones of Benin and one the other hand determined their seasonal evolution and evaluated their weight according to the cotton development stage. The density of insect pests and their damages were evaluated in cotton farms. A Correspondence Analysis was used to describe the relationship between insect pests and cotton phytosanitary zones (zone 1, zone 2, zone 3). The seasonal evolution of the identified insect pests was assessed using simple time series trend. Mann-Whitney test was used to compare the density of insect pests between cotton development stages. The results showed that Helicoverpa armigera and Diparopsis watersi were the major insect pests of the zone 1. Those major in the zone 2 were Bemisia tabaci, Dysdercus volkeri, Haritaloïdes derogata and Aphis gossypii and those major of the zone 3 were Thaumatotibia leucotreta, Pectinophora gossypiella, Polyphagotarsonemus latus and Earias spp. Following cotton development stage, the prevalence (% of cotton stalks attacked) of H. derogata in the phytosanitary zone 2 varied from 2.70 ± 0.67% during the vegetative stage to 0.6 ± 0.06% during the fruitification stage. The prevalence of H. derogata decreased significantly during the fruitification stage. The prevalence of P. gossypiella varied from 1.90±0.36 during the vegetative stage to 0.40±0.24 during the fruitification stage. The prevalence of P. latus varied from 4.33±0.76% during the vegetative stage to 1.17±0.52% during the fruitification stage in the cultivation zone 3. The number of P. gossypiella and the prevalence of P. latus significantly decreased from the vegetative stage to that of fruitification. Our results could be meaningful while developing effective fighting strategies against insect pests.
Keywords: spatial distribution; seasonal evolution; crops pests; development stage; biological cotton.